Til amerikanerne: I Guds, den Nåderike, den Barmhjertiges navn. - Laden, Osama Bin (K&K - Kultur og Klasse, 2008)
To the Americans: In this letter from 2002 Osama Bin Laden replies to unidentified American writers explaining why al-Qaeda is justified in attacking North American targets. The letter poses two questions: What are we fighting for? and What are we calling you to do, and what do we want from you? According to Bin Laden al-Qaeda is engaged in a fight responding to decades of Western aggression. Bin Laden presents a detailed account of the misdeeds that the United States are responsible for in the Middle East and in Afghanistan. The letter also denounces North American society as characterised by usury, debauchery, gambling, prostitution and environmental destruction. Finally Bin Laden provides the reader with a series of examples connected to the ‘war on terror’ where the United States does not live up to its own rhetoric: the detention of prisoners at Guantanamo, the suspension of civil liberties in the Patriot Act and the rejection of the Kyoto Accords.